Cardiac Tamponade due to Purulent Pericarditis - Jessica Anastasia Setiawan; Danayu Sanni Prahasti (Jurnal Kardiologi Indonesia, 2026)
Background: Purulent pericarditis, though uncommon in the antibiotic era, remains highly fatal when diagnosis or drainage is delayed. Its presentation often mimics viral hepatitis, sepsis, or parasitic infections—particularly in endemic, low-resource regions—leading to underrecognition. This case reported the development of purulent pericarditis with initial equivocal signs and symptoms, followed by progressive hemodynamic deterioration. Case Illustration: A 40-year-old previously healthy man presented with fever, dyspnea, stabbing chest and abdominal pain, and dark urine. Examination revealed jaundice, pericardial friction rub, and hepatosplenomegaly. Laboratory tests showed leukocytosis, hyperbilirubinemia, and elevated liver enzymes. Initial echocardiography demonstrated a 2-cm circumferential effusion without signs of tamponade. Two days later, despite stable symptoms, he developed hypotension with new fibrinous effusion and right atrium collapse. Emergency pericardiocentesis drained 1.7 L of thick, purulent fluid. Hemodynamics improved rapidly after drainage. Prednisone and colchicine were initiated once infection control was achieved to limit fibro-inflammatory response and reduce the risk of constriction. Liver function normalized, and follow-up echocardiography showed minimal residual effusion. At follow-up, the patient remained asymptomatic. Conclusion: This case highlights that purulent pericarditis can occur in immunocompetent individuals without typical risk factors, possibly from overlooked infection in low-resource settings. Hemodynamic collapse may occur even with small increases in pericardial effusion volume, owing to fibrin-induced pericardial stiffness and reduced compliance. Serial echocardiography is therefore critical when symptoms appear stable. Early pericardiocentesis is both diagnostic and therapeutic, reducing bacterial and inflammatory load, while carefully selected adjunctive anti-inflammatory therapy may prevent chronic constrictive sequelae.